Sanksi Pidana Terhadap Pemberi Kerja dalam Undang-undang No.11 Tahun 2020 tentang Cipta Kerja - Nyoman Sugiartha; Kalingga Maulana Ibrahim; I Putu Gede Seputra (Fakultas Hukum, Universitas Warmadewa, 2021)
The Job Creation Act is a new law that is causing controversy, especially among workers/workers because the Job Creation Bill is considered detrimental to workers due to the imbalance of power relations in making agreements. The purposes of this study are to reveal the legal arrangements against employers in Law No. 11 of 2020 concerning Job Creation and criminal sanctions against employers if they do not comply with the provisions of the Job Creation Act. The type of research used in this study uses a normative legal research type with a statutory approach and a conceptual approach. The techniques for collecting legal materials are recording, summarizing, and quoting techniques. Sources of data used in the form of secondary and primary data which are then analyzed qualitatively. The results of the study reveal that there are criminal sanctions for entrepreneurs who pay labor wages below the district/city minimum wage as stipulated in Article 185 paragraph 1 of the Job Creation Law, namely a criminal threat for violating the criminal provisions, namely imprisonment for a minimum period of 2 years and a maximum of 4 years in prison and/or a fine of at least 100 million and a maximum of 400 million